Syed Syeikh Ahmad al-Hadi’s Thought on Women’s Emancipation and Gender Equality: Re-Evaluation and Analysis - Hamisan @ Khair, Nur Saadah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Known as the early 20th century Malay-Muslim scholar, Syed Syeikh Ahmad al-Hadi (1867-1934) has written several works concerning women’s issues; including Faridah Hanom, Hikayat Anak Dara Ghasan, Hikayat Puteri Nurul‘Ain, Kitab Alam Perempuan and many others. The present study attempts to examine his thought on the emancipation of women and gender equality, since not many Malay scholars focus on a similar issue during his time. This paper discusses on the development of his idea through magazines and novels since the 1920s, which later gave impact to the Malay society from cultural, social, political as well as religious aspects. This study also highlights several factors which might influenced his thought by discovering his educational background and analysing his different methods of arguments applied in his writings. By using qualitative approach, the study concludes that Syed Syeikh Ahmad al-Hadi has integrated both Islamic and modern perspectives in his writings, particularly concerning women’s issues such as on the emancipation of women and gender equality. Although some of his ideas seem controversial, it was among the earliest effort to propose a change to Malay traditions, where women were often given a limited role in society, for they only had major roles in domestic affairs.